Social Panorama of Latin America 2016 - United Nations (United Nations, 2017)
The central theme of this edition of Social Panorama of Latin America is social inequality, seen as a fundamental challenge and obstacle to sustainable development. Some of the axes and aspects of social inequality are addressed, drawing attention to how they intersect with and reinforce one another. The different chapters will examine inequalities in the distribution of income (personal and functional) and property; inequalities over the course of the life cycle; time-use inequalities between men and women; and the situation of Afrodescendent populations as an example of ethnic and racial inequalities. Recent trends in the amount of public resources available to finance social policies capable of tackling poverty and inequality and of promoting inclusive social development are also analysed.